Daily electronic self-monitoring of subjective and objective symptoms in bipolar disorder—the MONARCA trial protocol (MONitoring, treAtment and pRediCtion of bipolAr disorder episodes): a randomised controlled single-blind trial. Issue 7 (24th July 2013) - Faurholt-Jepsen, Maria; Vinberg, Maj; Christensen, Ellen Margrethe; Frost, Mads; Bardram, Jakob; Kessing, Lars Vedel
Abstract : Introduction: Electronic self-monitoring of affective symptoms using cell phones is suggested as a practical and inexpensive way to monitor illness activity and identify early signs of affective symptoms. It has never been tested in a randomised clinical trial whether electronic self-monitoring improves outcomes in bipolar disorder. We are conducting a trial testing the effect of using a Smartphone for self-monitoring in bipolar disorder. Methods: We developed the MONARCA application for Android-based Smartphones, allowing patients suffering from bipolar disorder to do daily self-monitoring—including an interactive feedback loop between patients and clinicians through a web-based interface. The effect of the application was tested in a parallel-group, single-blind randomised controlled trial so far including 78 patients suffering from bipolar disorder in the age group 18–60 years who were given the use of a Smartphone with the MONARCA application (intervention group) or to the use of a cell phone without the application (placebo group) during a 6-month study period. The study was carried out from September 2011. The outcomes were changes in affective symptoms (primary), social functioning, perceived stress, self-rated depressive and manic symptoms, quality of life, adherence to medication, stress and cognitive functioning (secondary and tertiary). Analysis: Recruitment is ongoing. Ethics: Ethical permission has been obtained. Dissemination: Positive, neutral and negative findings of the study will be published. Registration details: The trial is approved by the Regional Ethics Committee in The Capital Region of Denmark (H-2-2011-056) and The Danish Data Protection Agency (2013-41-1710). The trial is registered at ClinicalTrials.gov as NCT01446406 .